Implementasi Kebijakan Program Keluarga Harapan (PKH) di Kecamatan Jekan Raya Kota Palangka Raya - Muhammad Riban Satia; Suhardi Suhardi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
In the implementation of the Harapan family Program, Several things need to be considered, ranging from how to the stages, the implementation capability, communication that awakened, conformity of implementation with existing guidelines, and the commitment of participants of PKH related Its obligations. Based on the results of the research that has been done, it can be concluded, namely: that the process of implementing the Program family hope in Jekan Raya Sub-district is done through several stages, namely starting from the selection and establishment of PKH participants, The initial meeting, the payment phase, the establishment of a group mother of PKH recipients, verification of commitments, suspension and cancellation, and complaints process. In general, the implementation of the Program family Harapan (PKH) in Jekan Raya subdistrict has been running well and smoothly. Where the process of each stage of implementation of this program has been run properly because it is done by referring to the procedures and mechanisms in the provisions of PKH. The success of PKH implementation in Jekan Raya sub-district is also not separated from its implementation role, communication that awakened, the characteristics of implementing agents as well as from participants of PKH itself in its commitment to carry out its obligations. Some obstacles or obstacles that occurred in the process of implementation of family Harapan Program (PKH) in Jekan Raya Sub-district is concerned with the problem of uncertainty payment date, as well as a cynical response or social jealousy of the community Participants of the PKH community.